2002
DOI: 10.1051/0004-6361:20021192
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive search for magnetic fields in B, A and F stars

Abstract: Abstract. Circular spectropolarimetric observations of 74 stars were obtained in an attempt to detect magnetic fields via the longitudinal Zeeman effect in their spectral lines. The sample observed includes 22 normal B, A and F stars, four emission-line B and A stars, 25 Am stars, 10 HgMn stars, two λ Boo stars and 11 magnetic Ap stars. Using the Least-Squares Deconvolution multi-line analysis approach , high precision Stokes I and V mean signatures were extracted from each spectrum. We find absolutely no evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
197
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 155 publications
(218 citation statements)
references
References 48 publications
20
197
1
Order By: Relevance
“…This small sample of HgMn stars also included the spectrum variable HgMn star α And with a magnetic field of the order of a few hundred Gauss. On the other hand, highresolution spectropolarimetric spectra of some HgMn stars, including α And, were used in studies of Shorlin et al (2002) and Wade et al (2006), where no detection was achieved using all metal lines together in the least-squares deconvolution multiline profile. Although strong large-scale magnetic fields have not generally been found in HgMn stars, it has never been ruled out that these stars might have tangled magnetic fields of the order of a few thousand Gauss with no net longitudinal component (e.g., Hubrig et al 1999;Hubrig & Castelli 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This small sample of HgMn stars also included the spectrum variable HgMn star α And with a magnetic field of the order of a few hundred Gauss. On the other hand, highresolution spectropolarimetric spectra of some HgMn stars, including α And, were used in studies of Shorlin et al (2002) and Wade et al (2006), where no detection was achieved using all metal lines together in the least-squares deconvolution multiline profile. Although strong large-scale magnetic fields have not generally been found in HgMn stars, it has never been ruled out that these stars might have tangled magnetic fields of the order of a few thousand Gauss with no net longitudinal component (e.g., Hubrig et al 1999;Hubrig & Castelli 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigations of magnetism in such stars (e.g. Borra & Landstreet 1980;Glagolevskij et al 1985;Shorlin et al 2002;Aurière et al 2010;Makaganiuk et al 2011) have found no convincing evidence for fields in this class of stars with uncertainties often in the range of a few G up to a few tens of G. Furthermore, α And has been specifically investigated with the MuSiCoS (13 observations, typical σ ∼ 30-60 G) and ESPaDOnS (5 observations, typical σ ∼ 6-19 G) spectropolarimeters without any significant detection of a nonzero longitudinal field or of any Stokes V signature indicative of a non-zero field ).…”
Section: Repeated Observations Of Non-magnetic Starsmentioning
confidence: 99%
“…They are found in a small fraction of these stars, exclusively among the chemically peculiar Ap/Bp stars (Wolff 1968;Shorlin et al 2002;Bagnulo et al 2006;Aurière et al 2010;Kochukhov et al 2013). They are mainly dipolar or low-order multi-polar fields, with polar strengths ranging from 300 G to 30 kG, most having fields of order 1 kG (e.g.…”
Section: Introductionmentioning
confidence: 99%